2018
DOI: 10.31901/24566322.2018/20.1-3.11
|View full text |Cite
|
Sign up to set email alerts
|

On the Unity of Behaviourism, Cognitivism and Constructivism in Teaching and Learning

Abstract: Information and Communication Technology has changed the way of learning and sharing the knowledge in the education sector. Students prefer to participate and learn in web based environment. But they can be benefitted in this environment only if they have internet self-efficacy. The objective of this paper is to construct an "Internet Self-efficacy Scale" which can be used to determine the internet related ability and skills of secondary school students. The internet self-efficacy scale was administered to 350… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 1 publication
0
12
0
Order By: Relevance
“…This study employed a deductive research design by testing the behaviourism learning theory (Bitektine, 2008) to determine how much the chemistry teachers had shifted from teacher-centred to learner-centred teaching methods (Imenda, 2018) during the implementation of the CBC in 10 selected secondary schools in the Gasabo District of Rwanda. Both qualitative and quantitative methods were used to understand the current situation in selected secondary schools in chemistry education (Creswell & Garrett, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…This study employed a deductive research design by testing the behaviourism learning theory (Bitektine, 2008) to determine how much the chemistry teachers had shifted from teacher-centred to learner-centred teaching methods (Imenda, 2018) during the implementation of the CBC in 10 selected secondary schools in the Gasabo District of Rwanda. Both qualitative and quantitative methods were used to understand the current situation in selected secondary schools in chemistry education (Creswell & Garrett, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…The development of training programs for ecommerce entrepreneurs is considered an important component of the "digital entrepreneurial revolution" in recent years [2]. Technically, training should provide relevant, timely information, and improve skills [3], yet studies have found that many ecommerce entrepreneurs face difficulties in applying their understanding although many have undergone training [4]. In Malaysia, the rapid growth of technology in recent years has seen a similar growth trend in entrepreneurial education and training [5] (see table 1).…”
Section: Introductionmentioning
confidence: 99%
“…The quality and relevance of training programmes are challenges faced by the government and the agencies involved [4], [9]. Consequently, the literature on digital entrepreneurship should include training evaluation and methods that fit the current technology business environment [10].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations